Inter-generational differentials in perceptions of intimate partner violence in Nigeria - Treasure C. I. Ntoimo; Beatrice Adeoye; Lorretta F. C. Ntoimo (PLoS ONE, 2025)
Despite global efforts, gender-based violence (GBV) remains a problem that affects millions of people, particularly women. The prevalence of GBV in Nigeria has not improved over time; women who experienced physical violence since age 15 increased from 28% in 2008 to 31% in 2018. Intimate partner violence (IPV) constitutes a large proportion of the GBV in Nigeria. Although perceptions of IPV have been studied, differentials in perceptions among the different generations of Nigerians are unknown. People’s perceptions of IPV are influenced by societal shifts and other factors that differ among people of various ages. This research examined inter-generational differentials in the perception of IPV in Nigeria. Data were obtained from the 2021 Nigeria Multiple Indicator Cluster Survey. A sample of 53,706 men and women was analyzed using descriptive statistics, and logistic regression models. The older generations of men and women in Nigeria have significantly better perceptions of IPV than the younger generation, but there is a significant variation at the sub-national level. The observed pattern is worrisome and calls for urgent action by the government to advance more positive perceptions of GBV in Nigeria if the country will make progress in reducing the prevalence of GBV and achieve a violence-free society.